1995
DOI: 10.1042/bj3070571
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of inhibition of Ca2+-ATPase by myotoxin a

Abstract: The peptide DCRQKWKCCKKGSG [myotoxin-(29-42)], corresponding to residues 29-42 of myotoxin a, inhibits the activity of the Ca(2+)-ATPase of skeletal muscle sarcoplasmic reticulum, with a Kd value of 19.4 microM at pH 7.5, in 100 mM KCl. The peptide YKQCHKKGGHCFPKEK, corresponding to residues 1-16 of myotoxin a, is a less potent inhibitor. Inhibition by myotoxin-(29-42) is reduced at low pH and at high ionic strength, suggesting that charge interactions are important in binding to the ATPase. Inhibition of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 53 publications
1
7
0
Order By: Relevance
“…We have shown that Cys-containing peptides can quench the fluorescence of the ATPase labelled with a variety of fluorescence probes [38]. Figure 2(B) shows the effect of PLB(25-52) on the intensity of the tryptophan fluorescence of the ATPase, as a function of the molar ratio of peptide to ATPase at a fixed molar ratio of DOPC to ATPase of 2000 : 1.…”
Section: Reconstitution Of the Atpase With Plb Cys − (1-52)mentioning
confidence: 99%
See 1 more Smart Citation
“…We have shown that Cys-containing peptides can quench the fluorescence of the ATPase labelled with a variety of fluorescence probes [38]. Figure 2(B) shows the effect of PLB(25-52) on the intensity of the tryptophan fluorescence of the ATPase, as a function of the molar ratio of peptide to ATPase at a fixed molar ratio of DOPC to ATPase of 2000 : 1.…”
Section: Reconstitution Of the Atpase With Plb Cys − (1-52)mentioning
confidence: 99%
“…We have shown that melittin and myotoxin inhibit the Ca# + -ATPase by decreasing the rate of dephosphorylation of the phosphorylated ATPase [38,39]. The rate of dephosphorylation can be determined either by first phosphorylating the ATPase with [$#P]P i at pH 6.0 in the absence of Ca# + and the presence of DMSO followed by mixing with an excess of a pH 7.5 buffer containing KCl and ATP to induce dephosphorylation, or by first phosphorylating the ATPase with [γ-$#P]ATP in the presence of Ca# + and then mixing with an excess of unlabelled ATP.…”
Section: Mechanism Of Inhibition Of the Atpase By Plb Cys − (1-52)mentioning
confidence: 99%
“…Tryptophan fluorescence was monitored (at 25°C) by exciting the sample at 280 nm and measuring the emission above 320 nm using a cut off filter. 4 , 100 M CaCl 2 , and 0.075 mg/ml ATPase. Two stocks of labeled ATP were made up to cover the range of ATP concentrations up to 100 M, with specific activities of 10 and 100 Ci/mol.…”
Section: Methodsmentioning
confidence: 99%
“…A recent report describes the role of PDC-109, the major secretory protein from bull seminal vesicles as a stimulator of bovine sperm membrane Ca 2+ -ATPase [19]. Apart from these, certain exogenous peptides like mellitin [1], myotoxin a [2], mastoparan [9] etc. are potent inhibitors of sarcoplasmic reticulum Ca 2+ -ATPase (SERCA).…”
Section: Introductionmentioning
confidence: 99%